Rural water supply and sanitation - World Bank (Washington World Bank, 1999)
Rural water supply and sanitation by the World Bank,as part of the Water Resources Management work dwells on the policy and constraints of this sector, institutional and financial issues related in sector reform process an advocates an approach to bring a
World Bank. South Asia region, Rural Development sector unit in collaboration with the Govt of India, Ministry of Rural Areas and Employment (The Rajiv GandhiNational Drinking water mission), Danida (Danish International Development Assistance)
Keywords: Water supply, Rural-India-Finance; Sanitation, Rural-India-Finance; Economic assistance-India